PENILAIAN HARGA SAHAM DENGAN ANALISIS CROSS SECTIONAL PADA PERUSAHAAN REAL ESTATE DAN PROPERTY - Mayasari, Desy (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to assess the share price reasonableness of the real estate and property companies by using cross sectional analysis based on the PER model which is adopted from the Elton-Gruber (1991) and Whitbeck-Kisor (1963) model by considering PBV factor. The simple linier regression analysis is used in this research as the regression analysis in the PER I model, while the multiple linear regressions analysis is used in this research as the regression analysis in the PER II model. The result which is obtained from the regression equation is PER = 25.722 â 10.228 growth for PER I model and PER = 11.519 â 6.833 growth + 13.719 DPR + 8.717 StdDev for PER II model. The prediction ability which is resulted either from PER I or PER II model have a significant of accuracy level. The result of classification is based on PER and by considering to the PBV factor on each issuer is: (1) the shares which are worth for buying is undervalued shares and has 1 < PBV < the industry average, (2) the shares which are worth for performing short selling is the overvalued shares and the share PBV are larger than the PBV average industry.Keywords: Cross Sectional Analysis, Price Earnings Ratio, Price to Book Value.